Penanaman Nilai-Nilai Iman Kristen Berbasis Pendidikan Agama Multikultural - Sugijanti Supit (THRONOS: Jurnal Teologi Kristen, 2022)
This study aims to obtain a practical strategic approach to instilling Christian values based on multicultural education for early childhood. This study's purpose was obtained using a descriptive qualitative method with a literature study approach that observes, analyzes, and manages various existing literature sources. To produce relevant educational development in early childhood education that integrates Christian values with an appreciation of pluralism. Viewed as a positive contribution to developing fundamental concepts and practices in early childhood related to Christian values, intelligence, and social skills to live in a multicultural society. Therefore Christian religious education must package an education that is creative and intelligent cognitively, affectively, and psychometrically according to the needs of early childhood to produce a transformation in the lives of early childhood who fear God and are virtuous. AbstrakPenelitian ini bertujuan untuk mendapatkan suatu pendekatan strategi yang efektif terkait penanaman nilai-nilai kristiani berbasis pendidikan multikultural untuk anak usia dini. Tujuan penelitian ini didapat dengan menggunakan metode kualitatif deskripsi dengan pendekatan studi literatur yang mengamati, menganalisa dan mengelolah berbagai sumber kepustakaan yang ada. Sehingga menghasilkan pengembangan pendidikan yang relevan dalam konteks pendidikan anak usia dini yang mengintegrasikan nilai-nilai kristiani dengan apresiasi terhadap kemajemukan. Dipandang sebagai suatu kontribusi positif bagi pembangunan konsep dan praktek nyata anak-anak usia dini terkait nilai-nilai kristiani  dan kecerdasan keterampilan sosial untuk hidup ditengah masyarakat yang berwarna muktikuktural.